PENGARUH METODE BERMAIN PERAN (ROLE PLAY) TERHADAP KETERAMPILAN BERBICARA SISWA KELAS III SDN 4 BUNGBULANG - Nur Choirunnisa, Fadila; Jenal Mutaqin, Ejen; Budi Irwan Taofik, De (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking skill is one of the essential language skills that elementary school students need to master. However, the speaking skills of third-grade students at SDN 4 Bungbulang were still relatively low, requiring the implementation of an effective learning method to improve them. One of the methods that can be applied is the Role Play method. This study aimed to determine the effect of the Role Play method on the speaking skills of third-grade students at SDN 4 Bungbulang. This study employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest-Posttest Design. The participants consisted of 26 third-grade students at SDN 4 Bungbulang. Data were collected through speaking skill tests administered before (pretest) and after (posttest) the implementation of the Role Play method. The assessed aspects included pronunciation, comprehension, voice volume, and body language. Data were analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and the N-Gain test. The results showed that the mean pretest score was 65.6 and increased to 83.7 in the posttest. The Wilcoxon Signed Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.000, which was lower than 0.05; therefore, H₀ was rejected and H₁ was accepted. This indicates that the Role Play method had a significant effect on the speaking skills of third-grade students at SDN 4 Bungbulang. In addition, the N-Gain score was 0.54, which falls into the moderate category, indicating that the Role Play method was moderately effective in improving students' speaking skills. Based on these findings, it can be concluded that the Role Play method has a significant and moderately effective impact on improving the speaking skills of third-grade students at SDN 4 Bungbulang.   Keywords: Role Play, Speaking Skills, Elementary School